Global Existence and Blowup of Solutions of Two Species Chemotaxis Model - Bhuvaneswari, V.; Balachandran, K. (Journal of Applied Nonlinear Dynamics, 2026)
This paper is devoted to obtain the global existence and blow up of solutions for two species chemotaxis system by the ratio of two solutions method. Our main concern is to show that the blow up properties of solutions depend only on the first eigenvalue.